Evaluation of retrobulbar blood flow in patients with age-related cataract; color Doppler ultrasonographic findings - Mohammadi A (Dove Medical Press, 2011)
Afshin Mohammadi1, Nilofar Khorasani2, Farzad Moloudi2, Mohammad Ghasemi-rad31Department of Radiology, Urmia University of Medical Sciences, Urmia, Iran; 2Student Research Committee, Urmia University of Medical Sciences, Urmia, Iran; 3Genius and Talented Student Organization, Student Research Committee, Urmia University of Medical Sciences, Urmia, IranObjectives: Cataracts are the most common cause of blindness worldwide, with cataract surgery being the most common ophthalmic procedure. To our best knowledge, this is the first case-control study with a large number of participants to evaluate ocular blood flow in patients with cataracts.Materials and methods: Color Doppler and duplex sonography of the orbital vessels was performed in 224 eyes of 112 patients with known bilateral age-related cataracts and in 76 eyes of 38 healthy age- and sex-matched volunteers.Results: The mean ± (standard deviation [SD]) of peak systolic velocity (PSV) of the ophthalmic artery in patients with cataracts (34.59 ± 22.49 cm/second) was significantly different to that in controls (52.11 ± 14.01 cm/second) (P < 0.001). The mean ± SD PSV of the central retinal artery in patients with cataracts (15.31 ± 4.93 cm/second) was significantly different to that in controls (9.61 ± 5.64 cm/second) (P < 0.001).Conclusion: The mean PSV and resistive index (RI) of the ophthalmic and central retinal arteries were lower in cataract patients when compared with normal subjects. This suggests that ocular hypoperfusion and changes in ocular hemodynamic may have a role in the formation of age-related cataracts.Keywords: retrobulbar blood flow, age-related, cataract, color Doppler ultrasonographic